1997
DOI: 10.1002/(sici)1098-2299(199702)40:2<185::aid-ddr8>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

WAY‐131256 is an orally active, efficacious, and in vivo functionally selective M1 agonist

Abstract: Computer modeling of carbachol docked in the human m1 receptor binding pocket has been used to discover a series of carbamate and thiocarbamate chiral, conformationally restricted analogues of carbachol based on azabicyclo[2.2.1]heptan‐3‐ol. These molecules have been evaluated for affinity and efficacy at human muscarinic receptors (m1–m5) transfected into a CHO cell line. None of these compounds was selective in binding. Thiocarbamate analogues had greater affinity for the m1 receptor subtype, but lower effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…WAY-131256 (20), a rigid carbamate analogue of acetylcholine, does not show selective affinity among the M 1 -M 5 receptor subtypes, and 20 is comparably potent agonist at both M 1 and M 2 receptors. 90 By contrast, in vivo studies suggested that 20 is selective for M 1 receptors compared to M 2 and M 3 receptors. Thiadiazole ester bioisosteres of aceclidine (21a,b) are as comparably efficacious and potent as the functionally selective M 1 agonist xanomeline (11b) in an M 1 cell line and have very little M 3 activity in vivo.…”
Section: Pharmacologymentioning
confidence: 97%
See 1 more Smart Citation
“…WAY-131256 (20), a rigid carbamate analogue of acetylcholine, does not show selective affinity among the M 1 -M 5 receptor subtypes, and 20 is comparably potent agonist at both M 1 and M 2 receptors. 90 By contrast, in vivo studies suggested that 20 is selective for M 1 receptors compared to M 2 and M 3 receptors. Thiadiazole ester bioisosteres of aceclidine (21a,b) are as comparably efficacious and potent as the functionally selective M 1 agonist xanomeline (11b) in an M 1 cell line and have very little M 3 activity in vivo.…”
Section: Pharmacologymentioning
confidence: 97%
“…Functional assays demonstrate that 19 is an agonist at M 1 −M 4 receptors but only a partial agonist at M 3 receptors. WAY-131256 ( 20 ), a rigid carbamate analogue of acetylcholine, does not show selective affinity among the M 1 −M 5 receptor subtypes, and 20 is comparably potent agonist at both M 1 and M 2 receptors . By contrast, in vivo studies suggested that 20 is selective for M 1 receptors compared to M 2 and M 3 receptors.…”
Section: Pharmacologymentioning
confidence: 99%